2018
DOI: 10.1002/aenm.201801090
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous CaCO3 Coatings Enabled Uniform Zn Stripping/Plating for Long‐Life Zinc Rechargeable Aqueous Batteries

Abstract: Zn‐based batteries are safe, low cost, and environmentally friendly, as well as delivering the highest energy density of all aqueous battery systems. However, the application of Zn‐based batteries is being seriously hindered by the uneven electrostripping/electroplating of Zn on the anodes, which always leads to enlarged polarization (capacity fading) or even cell shorting (low cycling stability). How a porous nano‐CaCO3 coating can guide uniform and position‐selected Zn stripping/plating on the nano‐CaCO3‐lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
757
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,045 publications
(770 citation statements)
references
References 28 publications
8
757
0
5
Order By: Relevance
“…Surface coating layer on anode acts as a protective layer to decrease the contact area between electrode and electrolyte, suppressing the HER and Zn corrosion during cycling. Zhi's group developed a porous nano‐CaCO 3 coating to achieve uniform Zn stripping/plating, and it is also found that the Zn dendrites formation would be facilitated with increased current densities, where the electrohealing methodology can be expected to eliminate already‐formed dendrites 38,39. The electrolyte optimization positively influences the performance of Zn anode by forming a smooth absorbed layer or decreasing the active of H 2 O in the electrolyte, leading to the dendrite‐free anode and guaranteeing the long cycle life of battery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface coating layer on anode acts as a protective layer to decrease the contact area between electrode and electrolyte, suppressing the HER and Zn corrosion during cycling. Zhi's group developed a porous nano‐CaCO 3 coating to achieve uniform Zn stripping/plating, and it is also found that the Zn dendrites formation would be facilitated with increased current densities, where the electrohealing methodology can be expected to eliminate already‐formed dendrites 38,39. The electrolyte optimization positively influences the performance of Zn anode by forming a smooth absorbed layer or decreasing the active of H 2 O in the electrolyte, leading to the dendrite‐free anode and guaranteeing the long cycle life of battery.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, various strategies have been proposed to solve the above challenges, which are mainly involving electrodebased solutions, [29][30][31][32] electrolyte-based solutions, [33][34][35][36] and elaborate interface engineer. [37][38][39][40] As for example, Archer's group reported the exceptional reversibility of Zn, which is prepared by employing graphene with a low lattice mismatch for Zn under an epitaxial mechanism. [29] Surface coating layer on anode acts as a protective layer to decrease the contact area between electrode and electrolyte, suppressing the HER and Zn corrosion during cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a series of intrinsic drawbacks including poor safety, environmental pollution derived from organic electrolytes as well as high cost from the scarce lithium resources remain challenges and hinder their in real energy storage systems. [14] Researchers have also proposed to suppress the growth of dendrites by constructing Zn anodes with a 3D structure. [15] However, its complex production processes and high production costs limit their wide applications.…”
Section: Introductionmentioning
confidence: 99%
“…During discharging, the blue‐colored PB coating is reduced into colorless and transparent PW by a K + and e − coinsertion reaction . At the same time, the Zn negative electrode loses its electrons and is electrochemically striped as Zn 2+ , to compensate the consumption of K + and e − by the cathodic reaction. In other words, this discharging reaction is also a spontaneous bleaching process with an electric energy output.…”
Section: Introductionmentioning
confidence: 99%